Belligerent GE-filters in GE-Algebras - Ravikumar Bandaru; Arsham Borumand Saeid; Young Bae Jun (Journal of the Indonesian Mathematical Society, 2022)
The notion of a belligerent GE-filter in a GE-algebra is introduced, and the relationships between a GE-filter and a belligerent GE-filter will be given. Conditions for a GE-filter to be a belligerent GE-filter are provided. The product and the union of GE-algebras are discussed and its properties are investigated.